Delineating the relationship between circulating osteoprotegerin and bone health in women with a pathogenic variant in BRCA1: A cross-sectional analysis - Mokhber, Aghaghia; Hall, Elizabeth; Uzelac, Aleksandra; Salmena, Leonardo; Cheung, Angela; Lubinski, Jan; Narod, Steven A; Kotsopoulos, Joanne (Bone Reports, 2024)
AbstractPurposeOsteoprotegerin (OPG) plays an important role in the inhibition of osteoclast formation and bone resorption. Studies have reported lower OPG levels among women with a pathogenic variant (mutation) in the BRCA1 gene, and thus, may be at greater risk for skeletal bone loss. Thus, we investigated the association between circulating OPG and two validated markers of bone health: 1) bone fracture risk score (FRAX) and 2) bone mineral density (BMD), among BRCA mutation carriers. MethodsWomen with a blood sample and clinical data were included in this analysis. An enzyme-linked immunosorbent assay (ELISA) was used to quantify serum OPG (pg/mL) and the 10-year risk of major osteoporotic fracture (FRAXmajor) and hip fracture (FRAXhip) (%) was estimated using a web-based algorithm. For a subset of women, lumbar spine BMD was previously assessed by dual x-ray absorptiometry (DXA)(T-score). A Mann–Whitney U test was used to evaluate the association between OPG and FRAX score, while linear regression was used to assess the association of OPG and BMD. ResultsAmong 701 women with a BRCA1 mutation, there was a significant (and unexpected) positive association between OPG levels and FRAX score (FRAXmajor: 2.12 (low OPG) vs. 2.53 (high OPG) P < 0.0001; FRAXhip: 0.27 (low OPG) vs. 0.44 (high OPG) P < 0.0001). In a subset with BMD measurement ( n = 50), low serum OPG was associated with a significantly lower BMD T-score (−1.069 vs. -0.318; P = 0.04). ConclusionOur findings suggest that women with inherently lower OPG may be at risk of lower BMD, the gold standard marker of bone disease. Due to the young age of our cohort, on-going studies are warranted to re-evaluate the association between OPG and FRAX in BRCA mutation carriers.